1994
DOI: 10.2466/pms.1994.78.2.611
|View full text |Cite
|
Sign up to set email alerts
|

Age, Cognitive Style, and Traffic Signs

Abstract: This study assessed the efficiency with which young and older adults of varying field dependence extract information from traffic signs. It also identified some visual attributes of signs which affect recognition time. Two experiments were conducted. In Exp. 1, digitized signs, embedded in rural and urban backgrounds, were presented on a computer monitor. Subjects indicated on which side a target sign had appeared. Analysis showed that recognition times were dependent on age and field-dependence scores. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Harano (1970) even illustrated that FDI was significantly related to a car driver's likelihood for accident involvement. Related to that, Lambert and Fleury (1994) demonstrated that FI individuals have faster reaction times to traffic signs.…”
Section: Field Dependence-independencementioning
confidence: 93%
“…Harano (1970) even illustrated that FDI was significantly related to a car driver's likelihood for accident involvement. Related to that, Lambert and Fleury (1994) demonstrated that FI individuals have faster reaction times to traffic signs.…”
Section: Field Dependence-independencementioning
confidence: 93%
“…So, complex perceptual stimulation may become overwhelming for people with reduced spatial abilities. Evidence for this comes from studies on driving skills in relation to visual clutter (Ho et al, 2001;McPhee et al, 2004) and visual complexity in the surrounding environment (Cantin et al, 2009;Keay et al, 2009;Lambert and Fleury, 1994): Older adults tend in fact to be slower and less accurate in searching road signs in traffic scenes with high clutter, measured as the number of objects in the visual field (McPhee et al, 2004), and to have increased cognitive workload in complex driving contexts, e.g. overtaking manoeuvres (Cantin et al, 2009).…”
Section: Environmental Layout Level Of Clutter and Spatial Cognitionmentioning
confidence: 98%
“…Traffic signs are essential components of the traffic control plan. They offer drivers necessary information on upcoming situations [ 1 , 2 , 3 ], thus playing a key role in highway safety. Highway construction is extending to western mountains areas in China, so the number of tunnels is increasing.…”
Section: Introductionmentioning
confidence: 99%